Egy új, mégis régi Németország születése - Maróti, Dávid (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
The year 1945 brought a radical change in the German history. The total defeat landed the Reich in difficulty. On the territory of the German Reich four entities have been established which could only get in touch with each other if the Allied Powers allowed them. The Allies took over the supreme power after Germany’s unconditional surrender. The old-new German political parties had to face the state building under hard circumstances such as the lack of sovereignty. The postwar chaos could be overcome in four years, therefore two new states have been rebuilt on the territory of the ‘Third Reich’. This study is restricted to present the birth of West Germany also known as Federal Republic of Germany from 1948 when the Western Powers officially announced the establishment of a federal state in the West German area.